Instruments of Debtstruction : A New Database of Interwar Debt - End, Nicolas (IMF Working Papers; Working Paper, 2019)
We construct a new, comprehensive instrument-level database of sovereign debt for 18 advanced and emerging countries over the period 1913-46. The database contains data on amounts outstanding for some 3,800 individual debt instruments as well as associated qualitative information, including instrument type, coupon rate, maturity, and currency of issue. This information can provide unique insights into various policies implemented in the interwar period, which was characterized by notoriously high debt levels. We document how interwar governments rolled over debts that were largely unsustainable and how the external public debt network contributed to the collapse of the international financial system in the early 1930s.